Political Parties and the State : The American Historical Experience - Shefter, Martin (Book collections on Project MUSE., 2001)
This book collects a number of Martin Shefter's most important articles on political parties. They address three questions: Under what conditions will strong party organizations emerge? What influences the character of parties--in particular, their reliance on patronage? In what circumstances will the parties that formerly dominated politics in a nation or city come under attack? Shefter's work exemplifies the "new institutionalism" in political science, arguing that the reliance of parties on patronage is a function not so much of mass political culture as of their relationship with public bu.